Suplementação de selênio e vitamina e em dietas para o pacu (Piaractus mesopotamicus) - Reis, Elenice Souza dos (2012)
This study aimed to evaluate the effect of levels of selenium and vitamin E on the productive performance, body earning and lipid stability of pacu. Were used 720 juvenile pacu (initial weight 43,52±1,03g), distributed in a completely randomized design with 36 cages of 1m³ each, installed in a masonry tank with 200m². For 100 days, the animals were fed until apparent satiation, twice a day, with based diet containing 26% of crude protein and 3000 Kcal of disgestible energy/kg. Each diet was supplemented with 4 levels of selenium (0, 1, 2 and 4 mg/kg of ration) combined with 3 levels of vitamin E (0, 100 and 200 mg/kg of ration), in a factorial scheme of 4x3, totaling twelve treatments, with three repetitions for each level. At the end of the experimental period, the fish fasted for 24 hours, and then performed the procedures for analysis of productive performance (total and standart lengths, weight gain, feed conversion ratio and survival) and of body earning (carcass, clean torso, head, visceral fat and hepatosomatic index). The clean torsos were stored under freezing for analysis of centesimal composition (humidity, protein, lipid and ash), and on days 60, 90 e 120 was performed analysis of lipid oxidation by thiobarbituric acid reactive substances. The levels of selenium (0, 1, 2 and 4 mg/kg of ration) combined with vitamin E levels (0, 100 and 200 mg/kg of ration) did not influence (p>0,05) on productive performance, body earning, physical and chemical composition of juvenile pacu (P. mesopotamicus). These parameters varied in accordance with the findings of other authors for the species. The interaction between levels of selenium and vitamin E did not influence (p>0,05) the lipid stability of clean torsos of pacu; however, evaluating only levels of vitamin E, the level of 200 mg vitamin E/kg of ration decreases the lipid oxidation in 90 and 120 days of storage. Just the level 0 Se + 0 vitamin E/kg of ration was influenced by storage time, and the highest rate of lipid oxidation was verified with 120 days of storage. The conclusion is that the level of 1 mg selenium + 200 mg vitamin E/kg of ration keeps the performance, body earnings and centesimal composition of juvenile pacu (P. mesopotamicus), besides reducing the lipid oxidation after 90 days of under freezing storage